Oncothermia as Personalized Treatment Option. (26th May 2013) - Szasz, Oliver; Andocs, Gabor; Meggyeshazi, Nora
Abstract : Oncothermia is a nanoheating technology personalized for individual status depending on the state, stage, grade, and other personal factors. The guiding line of the treatment keeps the homeostatic control as much effective as possible. One of the crucial points is the surface heat regulation, which has to be carefully done by the electrode systems. The applied stepup heating supports the physiological selection. Recognizing the hysteresis type of SAR-temperature, development of the protocol could be well conducted. Using the Weibull distribution function of the transport processes as well as considering the typical physiological relaxation time of the tissues, special protocols can be developed. It has wide-range applicability for every solid tumor, irrespective of its primary or metastatic form. It could be applied complementary to all the known oncotherapy methods. It is applicable in higher lines of the therapy protocols, even in the refractory and relapsed cases as well.